Pengaruh Interaksi Lintas Budaya Terhadap Terjadinya Miskomunikasi Nonverbal di Lingkungan Kampus - Salsa Nur Agus Meliyani (JURNAL ILMIAH NUSANTARA, 2025)
Cultural differences often trigger nonverbal miscommunication in crosscultural interactions that occur in campus environments. This article examines the influence of cross-cultural interactions on nonverbal miscommunication in various communication contexts. This study focuses on cultural differences, language styles, speech intonation and body language, which are the causes of nonverbal miscommunication, the negative impacts that arise and solutions that can be overcome. With a deeper understanding of nonverbal miscommunication, this article provides insight into how to develop oneself towards existing cultural differences, in order to maintain effective communication in cross-cultural interactions to build good and healthy social relationships.